Pengenalan Identitas Manusia Melalui Iris Mata Menggunakan Gray Level Co-occurence Matrix - Muh Aswan Abidin1; Kurniawan Nur Ramadhani; Anditya Arifianto (eProceedings of Engineering, 2018)
Abstrak Pada tugas akhir ini penulis menerapkan metode Gray Level Co-occurence Matrix sebagai ekstraksi ciri pada iris mata dan untuk mengklasifikasikan data menggunakan K-Nearest Neighbors serta Support Ve- ctor Machine. Dalam sistem ini menggunakan dataset UBIRIS Version 1 yang berjumlah 2000 gambar iris dari 100 individu. Hasil yang didapatkan dari pengujian ini menggunakan ekstraksi ciri Gray Level Co- occurence Matrix mampu menghasilkan F1 Score sebesar 71.10% Kata Kunci : Biometrics, Gray Level Co-occurence Matrix, K-Nearest Neighbors, Support Vector Machine Abstract In this final project the writer applies Gray Level Co-occurence Matrix method as feature extraction on iris and to classify data using K-Nearest Neighbors and Support Vector Machine. In this system using UBIRIS Version 1 dataset which amounts to 2000 iris images of 100 individuals. The results obtained from this test using feature extraction Gray Level Co-occurence Matrix capable of producing F1 Score of 71.10% Keywords: Biometrics, Gray Co-occurrence Matrix, K-Nearest Neighbor, Support Vector Machine